Arterial spin labeling demonstrates preserved regional cerebral blood flow in the P301L mouse model of tauopathy. Issue 4 (April 2022) - Kindler, Diana; Maschio, Cinzia; Ni, Ruiqing; Zerbi, Valerio; Razansky, Daniel; Klohs, Jan
There is growing evidence for the vascular contribution to cognitive impairment and dementia in Alzheimer's disease (AD) and other neurodegenerative diseases. While perfusion deficits have been observed in patients with Alzheimer's disease and tauopaties, little is known about the role of tau in vascular dysfunction. In the present study, regional cerebral blood (rCBF) was characterized in P301L mice with arterial spin labeling. No differences in rCBF in P301L mice compared to their age-matched non-transgenic littermates at mid (10–12 months of age) and advanced (19–21 months of age) disease stages. This was concomitant with preservation of cortical brain structure as assessed with structural T2 -weighted magnetic resonance imaging. These results show that hypoperfusion and neurodegeneration are not a phenotype of P301L mice. More studies are thus needed to understand the relationship of tau, neurodegeneration and vascular dysfunction and its modulators in AD and primary tauopathies.